Characterization of exopolysaccharides produced by Saccharomyces cerevisiae strains isolated from kefir samples and their rheological, antioxidant, and prebiotic properties - Goktas, Hamza; Agan, Cansu; Bekiroglu, Hatice; Bozkurt, Fatih (Springer, 2025)
Exopolysaccharides (EPSs), the fundamental components of kefir granules, are produced by microorganisms such as lactic acid bacteria and yeasts. S. cerevisiae is one of the most frequently isolated yeast species in kefir microflora. In this study, EPS production, characterization, and functional properties were examined from S. cerevisiae strains isolated from three different kefir samples. EPSs have a heteropolysaccharide structure, mainly composed of glucose and mannose units. NMR and FT-IR analyses confirmed the heteropolysaccharide structure of the EPSs. XRD analysis revealed that the EPSs had a semi-crystalline structure. The EPSs demonstrated shear-thinning flow behavior with increasing shear rate and had lower viscosity than guar gum. Conversely, endothermic peaks at higher temperatures indicated that the EPSs possessed high thermal stability. S. cerevisiae KY12 EPS showed higher antioxidant activity compared to other EPSs, with DPPH and FRAP values of 57.4% and 138.8 mg/mL, respectively (P <= 0.05). KY12 EPS also adsorbed 65.3% +/- 0.8% zinc, indicating a high capacity for heavy metal adsorption. EPSs enhanced the growth of probiotics L. rhamnosus and L. plantarum more than glucose and inulin, suggesting they could serve as potential prebiotic candidates. The results of this study imply that EPSs may be a new alternative for applications in food and pharmaceuticals.
Keywords: Kefir; Exopolysaccharide; S. cerevisiae; HPLC; NMR; Probiotic activity